Abolir les frontières en littérature jeunesse : la tentative des albums photographiques des années 1950 à travers l’exemple d’Horoldamba le petit Mongol - Laurence Le Guen (Strenae)
After the Second World War, photography—in exhibitions, the press, and publishing—had the goal of exploring the world and showing unity among the human race, due to a great pacifist movement initiated after the First World War. Youth literature was not to be outdone; photography in picture books was intended to convince young French readers (citizens of tomorrow), that the Other and they were similar. Drawing from Ergy Landau's book, Horoldamba le petit Mongol, published in 1957 by Calmann Levy, we will demonstrate how photography and narration in this project do not succeed in their ambition to unite humanity.